ANALYSIS OF CREATIVE ECONOMIC EMPOWERMENT IN MOJOKERTO DISTRICT - Fitra Ria Silvida (Journal of Finance, Economics and Business, 2023)
n responding to challenges in the post-pandemic era and in order to fulfill the mandate of the strategic plan and RPJMD related to finding new alternatives to drive the economy through the creative economy, Mojokerto Regency, among others, has made several efforts to empower and stimulate the growth of a new creative economy in the fields of promotion, socialization and also financing. In addition to these empowerment efforts, identifying creative economy potential, challenges in development, creative industry distribution areas and creative economy financing mechanisms are other elements examined in this study. This research uses descriptive qualitative research methods using primary and secondary data. The method used is interviews and data collection from the publication of agency/institutional documents. The purpose of this research is to find out the potential of creative industries in Mojokerto Regency, challenges in development, empowerment efforts, distribution areas, and creative economy financing mechanisms in Mojokerto Regency.